2012
DOI: 10.3899/jrheum.111510
|View full text |Cite
|
Sign up to set email alerts
|

Risks, Subtypes, and Hospitalization Costs of Stroke Among Patients with Systemic Lupus Erythematosus: A Retrospective Cohort Study in Taiwan

Abstract: Stroke risk and hospital care costs are considerably greater for patients with SLE than without. The relative risk of stroke is the highest in young patients with SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 27 publications
3
41
0
Order By: Relevance
“…Previous studies have demonstrated that both are higher in patients with SLE compared to controls (5,10,19,20). The current study confirms this observation, but also demonstrates a consistent change in the pattern of utilization over the 13 years of observation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previous studies have demonstrated that both are higher in patients with SLE compared to controls (5,10,19,20). The current study confirms this observation, but also demonstrates a consistent change in the pattern of utilization over the 13 years of observation.…”
Section: Discussionsupporting
confidence: 89%
“…Studies of health care utilization have consistently found that it is higher in SLE patients than in comparator groups of patients (4,5,10,16). Utilization may be influenced by a variety of factors, including disease severity (17) (higher in lupus nephritis [8,16] and neuropsychiatric lupus [11,16]), race and ethnicity (lower in Hispanics [18]), and the type of health care delivery (higher in the fee-for-service system [3]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taiwan began its National Health Insurance (NHI) program on March 1, 1995, in order to provide comprehensive health care to all citizens of Taiwan. As of December 2007, 22.6 million individuals, representing 98% of the Taiwanese population, had been enrolled in the program [8, 19]. The data on NHI claims include comprehensive demographic data, dates of clinical visits, and diagnostic codes, as well as details of prescriptions, examinations, and procedures, which are entered into the NHIRD; it is maintained by the Bureau of National Health Insurance, Taiwan.…”
Section: Methodsmentioning
confidence: 99%
“…To address this, we used the results from our meta-analysis on stroke risk associated with SLE11 and included our estimate in the pooled result to update the analysis. Pooling our study with Mok  et al 12 and Wang  et al 13 (not including Zöller  et al 14 because their data overlap with ours), the relative risk of stroke is 2.11 (1.22, 3.65), with I 2 of 49% and P for heterogeneity of 0.14. This indicates that SLE is associated with haemorrhagic stroke.…”
mentioning
confidence: 73%